Pengaruh Diskon, Online Customer Rating, Dan Promo Gratis Ongkos Kirim (Ongkir) Terhadap Keputusan Pembelian Pada Marketplace Shopee - Istiqomah, Roviqotul; Asral, Asral (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study aims to explain the effect of discounts, online customer ratings, and free shipping promos in influencing purchasing decisions on the Shopee marketplace and which one has the greatest influence on purchasing decisions on the Shopee marketplace study on Management Study Program Students class of 2020 Faculty of Economics and Business, Pelita Bangsa University. This study took a sample of 100 respondents who were consumers who had made buying or selling transactions through the Shopee marketplace where the respondents were students of the Management Study Program class of 2020, Faculty of Economics and Business, Pelita Bangsa University. For data collection by distributing questionnaires and literature studies. The type of research used is quantitative. The analysis methods used are validity test, reliability test, classical assumption test, multiple linear regression analysis and hypothesis testing. The results of the t test research show the t value of 1.438 with a significance of 0.154, which means that the first hypothesis is rejected and partially shows that there is no influence and insignificance between discounts on purchasing decisions. The online customer rating variable has t test results with a t value of 5.081 and a significance value of 0.000, which means that the second hypothesis is accepted and shows that there is a positive and significant influence between online customer rating on purchasing decisions.  The free shipping promo variable obtained the t test results with a t value of 3.968 and a significance value of 0.000, which means that the third hypothesis is accepted and shows that there is a positive and significant influence between free shipping promos on purchasing decisions. And it can be concluded that 64.9% of purchasing decisions are influenced by discount variables, online customer ratings, and free shipping promos while the remaining 35.1% of purchasing decisions are influenced by other variables not examined in this study.